Children's right to play sports in a safe and healthy environment - Aine Antti; Muhonen Jatta; Toivonen Virve (SPRINGER, 2022)
According to the United Nations Convention on the Rights of the Child (CRC), every child has a right to practise sports in a healthy, safe environment (art. 19). However, research indicates that child athletes experience various forms of violence in sports. Violence is particularly harmful to children, as the effects may be significant and long lasting. In addition, children often have difficulty identifying and reacting to violence. In this article, we first aim to shed light on the prevalence and implications of violence towards child athletes in sports. By child athletes, we mean athletes under the age of 18 (CRC art. 1). Thereafter, we discuss the following questions: (1) How does the CRC protect children in sports? (2) Can children's rights be effectively protected through sports self-regulation of sports bodies and legal remedies? (3) Who is responsible for safeguarding children's rights in sports? To answer these questions, we employ a multidisciplinary perspective that combines jurisprudence and sport psychology. In summary, we conclude that the CRC unequivocally prohibits all violence against children in all sectors of society, including sports. The responsibility for enforcing this prohibition lies with both member states and sports bodies. It is always the responsibility of adults. The full realisation of children's rights requires action on multiple fronts, including legislation, information, education and resources.